2012
DOI: 10.1111/j.1365-2826.2012.02306.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Deprivation in Rats is Associated with Corticotrophin‐Releasing Hormone (CRH) Promoter Hypomethylation and Enhances CRH Transcriptional Responses to Stress in Adulthood

Abstract: Exposure to stress during early development causes long-lasting alterations in behavior and hypothalamic pituitary adrenal (HPA) axis activity, including increased expression of corticotropin releasing hormone (CRH). To determine whether early life stress causes epigenetic changes in the CRH promoter leading to increased CRH transcription, 8-week old female and male rats, subjected to maternal deprivation (MD) between days 2 and 13 post-birth, were studied for HPA axis responses to stress and CRH promoter meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
136
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(145 citation statements)
references
References 42 publications
5
136
0
4
Order By: Relevance
“…This attenuation hypothesis (Trickett et al, 2010) is supported by a meta-analysis showing that the more time that had elapsed since trauma emerged, the lower a person's cortisol levels (Miller et al, 2007). Epigenetic alterations have been proposed as a mechanism for the stability of the long-term effects of early environmental influences in general (Mill and Heijmans, 2013) and the long-term setting of the HPA axis in particular (Chen et al, 2012;Murgatroyd et al, 2009;Turecki and Meaney, 2016;Weaver et al, 2004;Zhang and Meaney, 2010). Our own pilot study showed differences in DNA methylation patterns between the late adopted and early adopted groups, with large DNA methylation differences across several CpG sites in the promoter region of the cytochrome P450 2E1 gene (CYP2E1), involved in cholesterol and steroid synthesis, amongst other functions .…”
Section: Discussionmentioning
confidence: 93%
“…This attenuation hypothesis (Trickett et al, 2010) is supported by a meta-analysis showing that the more time that had elapsed since trauma emerged, the lower a person's cortisol levels (Miller et al, 2007). Epigenetic alterations have been proposed as a mechanism for the stability of the long-term effects of early environmental influences in general (Mill and Heijmans, 2013) and the long-term setting of the HPA axis in particular (Chen et al, 2012;Murgatroyd et al, 2009;Turecki and Meaney, 2016;Weaver et al, 2004;Zhang and Meaney, 2010). Our own pilot study showed differences in DNA methylation patterns between the late adopted and early adopted groups, with large DNA methylation differences across several CpG sites in the promoter region of the cytochrome P450 2E1 gene (CYP2E1), involved in cholesterol and steroid synthesis, amongst other functions .…”
Section: Discussionmentioning
confidence: 93%
“…Methylation of the proximal region of the promoter often correlates closely with a negative effect on gene expression (Vaissière et al, 2008). Moreover, deletions or mutations in these promoter regions cause a significant decrease in gene expression for Pomc, Crf and Crfr1 (Chen et al, 2012;Sotniko et al, 2014;Ehrlich et al, 2010). Hence, increased DNA methylation in the key epigenetic island in the promoter regions of the Pomc gene could have impaired the function of the hypothalamus resulting in reduced expression levels of this gene, as has been demonstrated in the PCAE offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Bisulfite pyrosequencing was not successful to detect Crfr1 gene methylation. The methods for Crf and Pomc bisulfite pyrosequencing were as described previously (Govorko et al, 2012;Chen et al, 2012). A MethPrimer program was used to assess the CpG island and bisulfite sequencing primers for these three genes (Supplementary Table S1).…”
Section: Bisulfite Pyrosequencingmentioning
confidence: 99%
“…Neonatal mother-offspring ties interruption resulted in decreased amount of mRNA CRF in hypothalamus and increased level of mRNA of GR in hippocampus of young rats (Liu et al 1997). sheep during ontogeny (Levine, Wiener 1988;Pihoker et al 1993;Plotsky, Meaney 1993;Liu et al 1997;Sevi et al 1999;Chen et al 2012;Lajud et al 2012). Increased ↑ ; Decreased ↓ amount or concentration of the chosen components of the HPA axis A different response of the HPA axis was shown to be dependent on the age of rats subjected to maternal separation.…”
Section: The Hypothalamic-pituitary-adrenal Axis Activity During Matementioning
confidence: 99%